Motiv och värdering vid köp av skogs- och lantbruksfastigheter i Västerbotten - Lundmark, Pär (2012)
The study has been done on behalf of and in cooperation with LRF Konsult. The purpose of the study was to try to find out how forest estate buyers valuated different parts of the estate at the time of the purchase and to see if it was possible to identify different trends between different kinds of purchasers. The study is delimited to Västerbotten County and all the purchases were made thru LRF Konsult. The background of the study is that the forest estate purchasers are paying more and more for the forest estates. The prices are often much higher than the net present value which means that they are paying for something more than just the timber value. The study is made with a questionnaire mailed to one hundred forest estate purchasers. Answers got returned from 48 of them. The questions in the questionnaire were about to how much and using what measurement the forest estate purchasers had valuated different parts of the estate at the purchasing moment. The results show that the main reason for purchasing the forest estate varies, most between the purchasers that were living in Västerbotten County and the purchasers that didn’t live in Västerbotten County. The purchasers that were living outside Västerbotten County thought that capital investment was the main reason for the purchase while the purchasers that were living in Västerbotten County thought that active use of the land was the main reason. Another result shows that the purchasers outside Västerbotten County valuated the forest lower than the purchasers living in Västerbotten. The buyers outside Västerbotten valuated the forest to 275 Swedish kronor per forest cubic meter while the purchasers from Västerbotten valuated the forest to 313 Swedish kronor per cubic meter.